Perception of second professional undergraduate medical students and teachers about pharmacy practical classes in pharmacology curriculum - Karmakar, Anindya; Mandal, Ananya; Mandal, Sonai; Gangopadhyay, Tanmoy; Naser, Syed Mohammad (International Journal of Basic & Clinical Pharmacology, 2019)
Background: The practice and teaching in the MBBS curriculum has changed over the last few decades and most of it caters to the making of the Indian Medical Graduate (IMG) and the first contact physician of the community. The most notable change in pharmacy in modern times has been the virtual disappearance of the preparation and compounding of medicines. Pharmacy practical classes still form a part of the MCI curriculum in Pharmacology undergraduate teaching in many states of India including West Bengal. This study was undertaken to assess the attitude of students as well as teachers towards continuation of these practical classes in the curriculum and possible alternatives. Methods: Second year pharmacology students were included in the study (n=143). Along with this 10 faculty members were provided a structured and pre-tested questionnaire to be answered anonymously. Results: It was seen that 89 percent students and 100 percent faculty members wanted these practical classes to be discontinued. The most popular alternative to these classes were ADR reporting from the faculty members (90%) and demonstration of clinical effects of drugs and dosage calculation (86%) among the students. Conclusions: Given the lessening importance and relevance of the pharmacy practical classes in today’s day to day practice, a change in curriculum and examination system in Pharmacology must be considered.